Assessment of outcome and complications of ultrasonography guided pigtail catheter drainage in management of liver abscess - Errey, Anil K.; Singh, Santosh K.; Sachan, Neha; Singh, Vandana (International Surgery Journal, 2020)
Background: Liver abscess (LA) is defined as an encapsulated collection of suppurative material within the liver parenchyma. Liver abscesses are most commonly due to bacterial, amoebic or mixed infections. Less commonly these may be fungal in origin. Liver abscess are associated with mortality of up to 20% and are categorized into various types based on aetiology, of which amoebic (ALA) and pyogenic (PLA) liver abscess are major types. The objective is to evaluate and assess the response of percutaneous pigtail catheter drainage in treatment of liver abscess and to document the complications of liver abscess (LA). Methods: The study was conducted on patients who were admitted from casualty and outpatient department with a diagnosis of liver abscess (LA). 100 patients of LA were included in the study. They were divided into two groups. Group 1 consists of LA patients without associated complications and Group 2 consists of LA patients with associated complications like rupture, jaundice, IVC compression, persistent or recurrent LA. Results: There were 88% males and 12% were females in the study. 30% patients had complications. Out of them, 14 (46.6%) patients of LA presented with intra-peritoneal rupture. 12 (40%) with jaundice, 2 (6.7%) with rupture into pleural cavity and 2 (6.7%) patients had IVC compression. (70%) had involvement of right lobe while minimum patients (12.9%) had bilateral lobe involvement in group 1 and (10%) had involvement of left lobe of liver in group 2. Conclusions: Pigtail insertion and percutaneous catheter drainage (PCD) of abscesses, peritoneal or pleural cavity are safe procedures. PCD is a good alternative to open surgical drainage.